Hungarian Monitoring, 30 January 1989 . [Magyar rádiófigyelő], 1989. január 30 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Warsaw Pact publishes European armed forces armament figures - Reactions to West Berlin elections on Sunday - Much of the Western press covers Imre Pozsgay's radio statement on Saturday regarding re-evaluation of 1956 revolution - Central Committee session in Belgrade - Afghan situation Domestic Affairs: - Reduction in numbers of the Hungarian army - Miklós Németh's speech at the Chamber of Commerce - Gyula Horn's Seoul talks - Mátyás Szűrös severely criticizes Romanian Party and state leadership - On freedom of conscience and religion: dialog between Hungarian Socialist Workers' Party (MSZMP) and church representatives at the Political College - Primary and middle school textbooks on 20th century history to be rewritten Economy: - Chamber of Commerce thinks it necessary to improve entrepreneurial conditions and transform competitive market economy - Restructuring of Pét Nitrogen Works Külpolitika: - A VSZ nyilvánosságra hozta az európai fegyveres erők fegyverzetének számát - A vasárnapi nyugat-berlini választások visszhangja - A nyugati sajtó nagy terjedelemben foglalkozott Pozsgay Imre szombati rádiónyilatkozatával, az 56-s forradalom átértékeléséről - KB ülés Belgrádban - Afganisztáni helyzet Belpolitika: - Létszámcsökkentés a néphadseregben - Németh Miklós beszéde a Gazdasági Kamarában - Horn Gyula szöuli tárgyalásai - Szűrös Mátyás keményen bírálta a román párt - És állami vezetést - A lelkiismereti és a vallásszabadságról - Párbeszéd az MSZMP és a magyar egyházak képviselői között a Politikai Főiskolán - Újra írják a századi történelemmel foglalkozó általános - És középiskolás tankönyveket Gazdaság: - A Gazdasági Kamara szükségesnek tartja a vállalkozási feltételek javítását, a versenyképes gazdasági szerkezet kialakítását - A Péti Nitrogénművek szanálása